Diﬀuse large B-cell lymphoma, NOS. Clinicopathological study in a cohort of peruvian patients - Dueñas Hancco, Daniela (2020)
Objective. The main of this research was to evaluate the clinicopathological characteristics of diffuse large B-cell lymphoma, no other specification (DLBCL, NOS) in a cohort of Peruvian patients diagnosed between 2005 and 2009. Methods. Seventy-two cases diagnosed with DLBCL, NOS, were studied at the National Institute of Neoplastic Diseases. Clinicopathological characteristics were evaluated and overall survival (OS) and other clinical parameters were compared according to cell of origin, Epstein-Barr virus (EBV) infection, and immunohistochemical (IHC) expression of MYC and BCL2. Results. There were 54 % women and 46 % men, with an average age of 65 years. 76 % were nodal, the majority cervical, and 24 % extranodal, with the stomach being the most affected site. The most frequent stages were II (35 %) and III (29 %), the majority with medium-high and high IPI. Histologically, almost all cases had centroblastic and immunoblastic morphology, with very few pleomorphic cases. There was a similar proportion of cases with germinal center (GCB) and non-germinal center (non-GCB) subtypes. GCBs and those in which the Epstein-Barr virus (EBER +) was found, had better OS than non-GCB and EBER-, respectively, although without statistical significance. Likewise, the cases with negative IHC for MYC and BCL2 had a better OS, and a higher percentage in early stages, but not without statistical significance. Conclusion. Our cases present characteristics like those described in the literature, although with a higher percentage associated with EBV and non-GCB cases. The small number of cases evaluated with IHC to determine subtypes and biomarkers may have limited the statistical analysis in this cohort of cases.